2014
DOI: 10.1371/journal.pone.0110959
|View full text |Cite
|
Sign up to set email alerts
|

The Expansion of the Pulmonary Rib Cage during Breath Stacking Is Influenced by Age in Obese Women

Abstract: ObjectiveTo analyze in obese women the acute effects of the breath stacking technique on thoraco-abdominal expansion.Design and MethodsNineteen obese women (BMI≥30 kg/m2) were evaluated by anthropometry, spirometry and maximal respiratory muscle pressures and successively analyzed by Opto-Electronic Plethysmography and a Wright respirometer during quiet breathing and breath stacking maneuvers and compared with a group of 15 normal-weighted healthy women. The acute effects of the maneuvers were assessed in term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 33 publications
(28 reference statements)
0
7
0
6
Order By: Relevance
“…The mean basal tidal volume (V T ) was calculated as the ratio of V E to RR (V E /RR), making it possible to calculate the rapid shallow breathing index (defined as the RR/V T ratio). 15 …”
Section: Methodsmentioning
confidence: 99%
“…The mean basal tidal volume (V T ) was calculated as the ratio of V E to RR (V E /RR), making it possible to calculate the rapid shallow breathing index (defined as the RR/V T ratio). 15 …”
Section: Methodsmentioning
confidence: 99%
“…26,27 According Jalayondeja et al, the body weight is a factor that should be considered as a predictor of MRP, for the bodily changes due to the thinness or overweight/obesity. 28 However, the direct influence of weight or BMI on the strength generation capacity of the respiratory muscles is still debated by several authors 29,30 : while some argue for a possible increase, hypothetically explained by a mechanism of muscle fibers adaptation resulting in an effect of longterm 'training,' [31][32][33] other studies have reported no effect of obesity on the respiratory muscles, 34,35 stimulating further discussion. Therefore, the present authors option to include in the study a population sample of normal weight individuals, overweight, stage I obesity, stage II obesity and stage III obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Age: age was considered a covariate in these analyses because it is related to respiratory muscle strength and to childbirth [3,1016,23].…”
Section: Methodsmentioning
confidence: 99%
“…Aging is a dynamic and progressive process, influenced by physiological, socioeconomic, and biological factors [1,2]. Among physiological factors linked to aging, numerous alterations in the respiratory system negatively impact respiratory volumes and capacities [3], contributing to the greater burden of morbidities commonly observed in this population [4].…”
Section: Introductionmentioning
confidence: 99%